Cercospora habenariicola sp. nov. and some new records of cercosporold fungi from Thailand - Meeboon J. (2014)
Several cercosporoid hyphomycetes were found during field examinations in northern Thailand, including the new species Cercospora habenariicola as well as Passalora atrides, P. centrosematis and Pseudocercospora cupheae, which are new to Thailand.